Revisiting debt-led and export-led growth models: A sectoral balances approach - Jan Behringer; Till van Treeck (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2018)
In this paper, we revisit the macroeconomic foundations and political economy of national growth models. We challenge the Kaleckian framework underpinning the emergent growth model literature in comparative political economy, which focuses primarily on the functional income distribution (wages versus profits), while ignoring personal income distribution (inequality across private households). Using the examples of the "export-led" and "debt-led" growth models of Germany and the United States, we show how institutional differences can help explain why different countries developed different patterns of income distribution and how income distribution and institutions interacted to generate financial imbalances in different sectors of the economy (i.e., the private household sector, the private corporate sector, and the government sector).
Keywords: D3; J5; P5; 330; Growth models; financial balances; functional income distribution; personal income distribution; institutions